Minoxidil-Coated Lysozyme-Shelled Microbubbes Combined With Ultrasound for the Enhancement of Hair Follicle Growth: Efficacy In Vitro and In Vivo - Ai-Ho Liao; Ai-Ho Liao; Yu-Jhen Huang; Ho-Chiao Chuang; Chih-Hung Wang; Chih-Hung Wang; Chih-Hung Wang; Cheng-Ping Shih; Chien-Ping Chiang; Chien-Ping Chiang (Frontiers Media S.A., 2021)
Lysozyme (Lyz) is an antimicrobial peptide, a safe adjunct, and it has been indicated that Lyz can promote vibrissae follicle growth by enhancing the hair-inductive capacity of dermal papilla cells in mice. The present study produced a new type of minoxidil (Mx)-coated antifungal Lyz-shelled microbubble (LyzMB) for inhibiting bacteria and allergies on the oily scalp. The potential of Mx-coated LyzMBs (Mx-LyzMBs) combined with ultrasound (US) and the role of LyzMB fragments in enhancing hair follicle growth were investigated. Mx grafted with LyzMBs were synthesized and the loading efficiency of Mx on cationic LyzMBs was 20.3%. The biological activity of Lyz in skin was determined using an activity assay kit and immunohistochemistry expression, and the activities in the US+Mx-LyzMBs group were 65.8 and 118.5 μU/mL at 6 and 18 h, respectively. In hair follicle cell culture experiments, the lengths of hair follicle cells were significantly enhanced in the US+Mx-LyzMBs group (108.2 ± 11.6 μm) compared to in the US+LyzMBs+Mx group (44.3 ± 9.8 μm) and the group with Mx alone (79.6 ± 12.0 μm) on day 2 (p < 0.001). During 21 days of treatment in animal experiments, the growth rates at days 10 and 14 in the US+Mx-LyzMBs group increased by 19.4 and 65.7%, respectively, and there were significant differences (p < 0.05) between the US+Mx-LyzMBs group and the other four groups. These findings indicate that 1-MHz US (applied at 3 W/cm2, acoustic pressure = 0.266 MPa) for 1 min combined with Mx-LyzMBs can significantly increase more penetration of Mx and LyzMB fragments into skin and enhance hair growth than Mx alone.